Sistem Pakar Mendiagnosa Gangguan Mental pada Diri Seseorang Mengunakan Metode Certainty Factor - Nopi Purnomo Nopi; Musthafa Haris Munandar; Feri Irawan; Januardi Rosyidi Lubis (Journal of Applied Computer Science and Technology)
People with mental disorders are very much starting in Indonesia, the results of health research in 2015, 1,193,151 people or 0.467% of the population who suffer from mental disorders. This mental disorder disease should not be silenced anymore, must be followed up or minimized in order to improve health conditions in Indonesia. The poverty rate in Indonesia until now is still relatively high and makes it difficult for people to deal with mental disorders. As for minimizing the handling of this mental disorder, it is very suitable to build an expert system using the certainty factor method, which is a method that defines a measure of capacity for a fact or rule, in expressing the level of confidence of an expert on a problem that is being faced by a patient or sufferer and can also be used as a benchmark of the results of the diagnosis of a disease suffered. By making this expert system, it can be useful for many people and can know clearly about mental disorders from symptoms and solutions based on a website and using PHP programming with a MySQL database. The results of the study using the certainty factor method with tests that have been carried out by the user or users are that the type of mental disorder suffered is the type of schizophrenia with a 56% certainty rate.